DIALEKTIKA REGULASI DAN TRADISI DALAM PELAYANAN PERKAWINAN DI KUA Dialectic of Regulation and Tradition in Marriage Services at The Office of Religious Affairs (KUA) - Syamsurijal Syamsurijal (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
The government has tried to improve marriage services, among others through Government Regulation (Peraturan Pemerintah) No. 48/2014 and Regulation of the Minister of Religious Affairs (Peraturan Menteri Agama) No.24/2014 which both related to the cost of marriage and reconciliation (rujuk). Those rules aim to omit illegal levies and gratification culture in the marriage process at the Office of Religious Affairs (KUA). But these new rules are precisely problematic when they are practiced in a community that has distinctive traditions in performing marriage events. This study is aimed to find out how the KUA runs these rules relating to the challenges of culture and community traditions. It uses qualitative approach on KUA in District Majene of West Sulawesi Province. The important findings of this study show that 1) the rules related to the costs of marriage are not yet fully socialized to the community; 2) response of KUA resources is good enough but not supported by adequate marriage facilities; 3) the community tradition in the marriage must be renegotiated by KUA officers to not violate the rules while still respecting the existing traditions.